The use of satellite remote sensing and GIS for assisting flood risk assessment - a case study of Agriokalamin catchment area in Paphos-Cyprus - Hadjimitsis, Diofantos G. (My University, 2007)
The main aim of this study is to evaluate the feasibility of utilizing satellite remote sensing and GIS tools to assist the technical flooding aspects of the catchment area of Agriakalamin River located in Kissonerga Village in Paphos-Cyprus. The remote sensing technique has been used to quantify the actual increase in urban area over the past forty three years. The Agriokalamin River area in Kissonerga Village in Paphos- Cyprus has been chosen as the study area. By analyzing the temporal satellite imageries and the observed meteorological and hydrologic data of the catchment, the local authorities can use the proposed methodology to investigate and assessing all the catchment areas versus the urbanization. The results of this study will encourage decision makers or the local authorities to consider land use planning as an effective non-structural measure for flood risk mitigation. Remotely sensed data such as aerial photos, Landsat-5 TM and Quickbird image data have been used to track the urbanization i.e. building activities near the catchment area (urbanization factor for the years 1963-2006: 0.9 % -27.0 %). GPS measurements have been used to locate in-situ the boundaries of the catchment area. Indicative flood risk assessment study was applied
Keywords: Remote sensing; Geographic information systems; Risk assessment; Satellites; Hydrology; Urbanization